2020
DOI: 10.1371/journal.pone.0225289
|View full text |Cite
|
Sign up to set email alerts
|

Two common disease-associated TYK2 variants impact exon splicing and TYK2 dosage

Abstract: TYK2 belongs to the JAK protein tyrosine kinase family and mediates signaling of numerous antiviral and immunoregulatory cytokines (type I and type III IFNs, IL-10, IL-12, IL-22, IL-23) in immune and non-immune cells. After many years of genetic association studies, TYK2 is recognized as a susceptibility gene for some inflammatory and autoimmune diseases (AID). Seven TYK2 variants have been associated with AIDs in Europeans, and establishing their causality remains challenging. Previous work showed that a prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 70 publications
0
35
0
Order By: Relevance
“…The A allele of the rs2304256 causes a substitution of valine to phenylalanine at position 362 in the JAK-homology 4 (JH4) region, which is a crucial domain for interaction of TYK2 with IFNAR1 and its function, maintaining the expression of IFNAR1 on cell membranes ( Tao et al, 2011 ; Marroqui et al, 2015 ). Li et al (2020 ) showed the rs2304256 A allele affects the TYK2 pre-mRNA processing since it destroys a putative exonic splicing enhancer; thus, promoting the inclusion of exon 8 in the mRNA, which is essential for TYK2 binding to cytokine receptors. Marroqui et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The A allele of the rs2304256 causes a substitution of valine to phenylalanine at position 362 in the JAK-homology 4 (JH4) region, which is a crucial domain for interaction of TYK2 with IFNAR1 and its function, maintaining the expression of IFNAR1 on cell membranes ( Tao et al, 2011 ; Marroqui et al, 2015 ). Li et al (2020 ) showed the rs2304256 A allele affects the TYK2 pre-mRNA processing since it destroys a putative exonic splicing enhancer; thus, promoting the inclusion of exon 8 in the mRNA, which is essential for TYK2 binding to cytokine receptors. Marroqui et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 3 previous meta-analyses ( Tao et al., 2011 ; Lee and Bae, 2016 ; Yin et al, 2018 ), including only 3 to 5 studies with SLE patients, were not able to show any association between this SNP and SLE. This SNP is located in intron 7 of TYK2 gene, most specifically 36 nt upstream of the intron 7/exon 8 boundary ( Li et al, 2020 ). The rs12720270 SNP is in strong LD with the functional rs2304256 and the rs280519 SNPs ( Contreras-Cubas et al, 2019 ; Li et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rs2304256 (V362F, C>A) is a missense variant located in exon 8 that is part of the FERM domain. It was suggested that this SNP reduces interaction between TYK2 and interferon α/β receptor 1 (IFNAR1) [59,60]. The TYK2 gene expression levels increased modestly in whole blood and adrenal gland of those carrying the A allele [60].…”
Section: Rs2304256mentioning
confidence: 99%
“…It was suggested that this SNP reduces interaction between TYK2 and interferon α/β receptor 1 (IFNAR1) [59,60]. The TYK2 gene expression levels increased modestly in whole blood and adrenal gland of those carrying the A allele [60]. There is evidence that the A allele of rs2304256 is a protective variant against T1D in those of European ancestry [61].…”
Section: Rs2304256mentioning
confidence: 99%